A new Time-of-Flight mass measurement project for exotic nuclei and ultra-high precision detector development - Sun Bao-Hua (EPJ Web of Conferences, 2016)
The time-of-flight (TOF) mass spectrometry (MS), a high-resolution magnetic spectrometer equipped with a fast particle tracking system, is well recognized by its ability in weighing the most exotic nuclei. Currently such TOF-MS can achieve a mass resolution power of about 2×10−4. We show that the mass resolution can be further improved by one order of magnitude with augmented timing and position detectors. We report the progress in developing ultra-fast detectors to be used in TOF-MS.